Comparison of exchange rate volatility in the spot and forward markets. - Lim, Raymond Kiat Jiang. (2008)
This paper seeks to compare the spot and forward exchange rate volatility of the major currencies. Under the assumption of non-stochastic interest rates, if the currency markets are efficient in the sense that it is not possible to arbitrage between the two markets, the volatility in the two markets should not be significantly different from each other.